Effect of Music and Aromatherapy Applied in Palliative Care on Symptom Management: A Systematic Review - Duygu Akbas Uysa and Fisun Senuzun Aykar (Professor Despina Sapountzi-Krepia, 2024)
Effect of Music and Aromatherapy Applied in Palliative Care on Symptom Management: A Systematic Review